Water soluble vitamins : Clinical research and future application - Stanger, Olaf (Subcellular Biochemistry, 2012)
The discovery of vitamins in the early 1900s, their later chemical characterization and the clarification of pivotal metabolic functions are sequential aspects of a brilliant chapter in the history of modern nutritional sciences and medicine. The name, derived from "vital-amines", indicates their elementary metabolic key functions in human metabolism. Vitamins are truly families of compounds, which include precursors and various free and bound forms, all with individual roles in metabolism and function. A more recent approach therefore searches for the components, the understanding of their roles in physiology and pathology as well as looking for novel pharmacological applications. When used properly, vitamins are, indeed, "magical" substances. Due to their efficacy, they should therefore be regarded as drugs with effects and side effects to be weighted against each other. Today, it is not the previously fatal deficiency-associated diseases that are in the focus of interest, but rather the relation of suboptimal vitamin bioavailability to chronic disease. This is complicated by genetic susceptibility, lifestyle, and the presence or absence of health-compromising habits, such as smoking. In turn, the development and application of new and more sensitive and specific assays further enable us to look more closely into the many functions of vitamins. Water soluble vitamins are complex molecular structures and even today, many areas in vitamin biochemistry are not yet fully understood. Novel effects and functions of vitamins remain and continue to be discovered. This book presents most recent research results and fascinating new knowledge on the role and effects of the water soluble vitamins in man. Some of the most distinguished chemists, biochemists, biologists and clinicians have contributed valuable chapters sharing unexpected novel insights into the biochemistry, (epi)genetics, metabolism, and function of water soluble vitamins, with their potential for clinical applications. Thus, physicians, clinicians, scientists, researchers, epidemiologists. nutritional specialists and health professionals alike will find stimulating and fascinating new insight in the many roles that water soluble vitamins play in human health and disease.